What was Killing Babies in Ipswich Between 1872 and 1909? - Eilidh Garrett; Alice Reid (Historical Life Course Studies)
This paper examines the causes of infant mortality for the port town of Ipswich between 1872 and 1909. Ipswich is the only town in England for which a complete run of computer-readable, individual-level causes of death are available in the late 19th and early 20th century. Our work makes use of the ICD10h coding system being developed to contribute to two projects: Digitising Scotland (University of Edinburgh) and SHiP — Studying the history of Health in Port Cities (Radboud University, Nijmegen). We consider annual and quinquennial mortality rates amongst Ipswich's youngest residents by age, sex, seasonality and cause. The individual causes of death not only offer insight into conditions in the town, but also highlight questions concerning how best to interpret the information provided when both medical terminology and registration practices were changing over the decades of the study. Ipswich infant mortality rates very closely mirrored those of England as a whole, rather than the most unhealthy large cities, such as Liverpool or Manchester. It becomes clear that birth itself was a major cause of neonatal, even some post-neonatal, deaths. While water-food borne diseases killed large numbers in the summer months, it was the ever-present airborne diseases which carried off a greater number of small victims. Although the records offer a rich vein of data to explore, some causes of death, such as convulsions and teething, remain enigmatic and require further research.